Adverse childhood experiences, family relationship and generalized anxiety in the youth population in Hong Kong. (13th April 2021) - Tang, W.C.; Wong, C.S.; Chang, W.; Hui, C.L.; Chan, S.K.; Lee, E.H.
Abstract : Introduction: Adverse childhood experiences (ACEs) are shown to be risk factors for developing anxiety later in life. However, one's family relationship acts as a protective factor between ACEs and anxiety. Objectives: The present study examines the interaction between ACEs and family relationship and their effect on generalized anxiety (GA) amongst the youth population in Hong Kong. Methods: Participants aged 15-24 were recruited from a population-based epidemiological study in Hong Kong. GA in the past two weeks was assessed using GAD-7, while ACEs were measured using the childhood section of Composite International Diagnostic Interview screening scales (CIDI-SC), encompassing parental psychopathology, physical, emotional, sexual abuse, and neglect before age 17. Family relationship was measured by the Brief Family Relationship Scale (BFRS). Linear regression and a two-way ANCOVA were conducted to examine the association between ACEs, family relationship and GA, while adjusted for age and gender. Results: 633 (70.7%) out of 895 participants had any ACEs. ACEs significantly predicted GAD-7 scores (Β=1.272, t(891)=4.115, p<.001). Two-way ANCOVA reported a significant interaction effect of ACEs and family relationship on GA (F(1, 889)=4.398, p=.036), namely those who had any ACEs and poorer family relationship scored higher in GAD-7 (p<.001), whereas there was no difference in family relationship for those without ACEs on GA (p=.501). Conclusions: ACEs increases the vulnerability to GA later in life. However, its effect on anxiety decreases when one has a better family relationship. This suggests a possible moderating role of family relationship in developing GA among younger people.